Silicon Enhances Biomass and Grain Yield in an Ancient Crop Tef [Eragrostis tef (Zucc.) Trotter] - Ligaba-Osena, Ayalew; Guo, Wanli; Choi, Sang Chul; Limmer, Matthew Alan; Seyfferth, Angelia L.; Hankoua, Bertrand B. (Frontiers in Plant Science, 2020)
Silicon (Si) is one of the beneficial plant mineral nutrients which is known to improve biotic and abiotic stress resilience and productivity in several crops. However, its beneficial role in underutilized or ‘orphan’ crop such as tef [Eragrostis tef (Zucc.) Trotter] has never been studied before. In this study, we investigated the effect of Si application on tef plant performance. Plants were grown in soil with or without exogenous application of Na2SiO3 (0, 1.0, 2.0, 3.0, 4.0, and 5,0 mM), and biomass and grain yield, mineral content, chlorophyll content, plant height, and expression patterns of putative Si transporter genes were studied. Silicon application significantly increased grain yield (100%) at 3.0 mM Si, and aboveground biomass yield by 45% at 5.0 mM Si, while it had no effect on plant height. The observed increase in grain yield appears to be due to enhanced stress resilience and increased total chlorophyll content. Increasing the level of Si increased shoot Si and Na content while it significantly decreased the content of other minerals including K, Ca, Mg, P, S, Fe, and Mn in the shoot. A slight decrease in grain Ca, P, S and Mn was also observed with increasing Si treatment. The increase in Si content with increasing Si levels prompted us to analyze the expression of Si transporter genes. The tef genome contains seven putative Si transporters which showed high homology with influx and efflux Lsi transporters reported in various plant species including rice. The tef Lsi homologues were deferentially expressed between tissues (roots, leaves, nodes, and inflorescences) and in response to Si, suggesting that they may play a role in Si uptake and/or translocation. Taken together, these results show that Si application improves stress resilience and yield and regulates the expression of putative Si transporter genes. However, further study is needed to determine the physiological function of the putative Si transporters, and to study the effect of field application of Si on tef productivity.